The combined effects of superchilling and packaging on the shelf life of lamb. (November 2017) - Bellés, M.; Alonso, V.; Roncalés, P.; Beltrán, J.A.
Abstract: The aim of this study was to evaluate the effect of superchilled storage at − 1° on the shelf life of lamb slices packaged in an O2 enriched (40% O2 /30% CO2 /30% Ar) or in an anaerobic atmosphere (vacuum skin packaging). Physicochemical, microbial and sensory analyses were performed. The effect of superchilled storage on lamb stability differed depending on the atmosphere surrounding the product. Superchilled (− 1 °C) slices of lamb showed lower microbial counts than those refrigerated at 4 °C in both packaging conditions. Moreover, meat stored at − 1 °C had a higher colour stability under vacuum. Superchilled storage combined with an O2 enriched atmosphere increased the rate of lipid oxidation, which reduced the shelf life reached by refrigerating at 4 °C. Vacuum skin packaging strongly inhibited lipid oxidation independently of storage temperature. Thus, superchilled storage extended the shelf life at least twice compared to storage at 4 °C under anaerobic conditions while it was disadvantageous when an O2 enriched atmosphere was used. Highlights: Superchilling at − 1 °C affected lamb quality depending on packaging method. Vacuum skin packaging (VSP) inhibited lipid oxidation at − 1 and 4 °C. Superchilling increased lipid oxidation in high O2 MAP. Microbial growth was strongly reduced by superchilling. Superchilling together with VSP extended the shelf life to 28 days.